Mother-Scholar (Re)imagining K-12 Education - Lapayese, Yvette V.; SpringerLink (Online service) (Rotterdam : SensePublishers : Imprint: SensePublishers, 2012)
Mother-Scholar presents another way of knowing. The book illuminates the narratives of prominent mother-scholars in the discipline of education who are determined to (re)imagine a different educational space not only for their own children, but for all children. Today$1 (Bs schools are male-centered institutions in which standardized testing, rational mind, and emotionless space prevent children from realizing their full potential as creative, intelligent and soulful beings. Mother-scholars in the discipline of education assert that when motherhood and intellect confront and inform each other, a new thinking emerges to capture the possibility of humanizing education beyond the private relationships between mothers and children.s
Keywords: Education; Education; Education (general).